Platelet count as a predictor of metastasis and venous thromboembolism in patients with cancer - Sylman, Joanna L. (Converg Sci Phys Oncol, 2017)
Platelets are anucleate cells in the blood at concentrations of 150,000 to 400,000 cells/µL and play a key role in hemostasis. Several studies have suggested that platelets contribute to cancer progression and cancer-associated thrombosis. In this review, we provide an overview of the biochemical and biophysical mechanisms by which platelets interact with cancer cells and review the evidence supporting a role for platelet-enhanced metastasis of cancer, and venous thromboembolism (VTE) in patients with cancer. We discuss the potential for and limitations of platelet counts to discriminate cancer disease burden and prognosis. Lastly, we consider more advanced diagnostic approaches to improve studies on the interaction between the hemostatic system and cancer cells.